2D Co-crystallization of molecular homologues promoted by size complementarity of the alkyl chains at the liquid/solid interface. Issue 32 (5th August 2019) - Li, Shu-Ying; Yang, Xue-Qing; Chen, Ting; Wang, Dong; Zhu, Guang-Shan; Wan, Li-Jun
Abstract : Co-crystallization of organic molecules is an important strategy for the fabrication of molecular materials. Abstract : Co-crystallization of organic molecules is an important strategy for the fabrication of molecular materials. In this contribution, we investigated the mixing behavior of 5-(benzyloxy)-isophthalic acid homologues (BIC-C n, n = 6, 8, 10, 12, and 14) at the liquid/solid interface using a scanning tunneling microscope. Deposition of the single component of BIC-C n always results in typical honeycomb networks, whereas co-deposition of two BIC-C n homologues leads to hybrid double-walled honeycomb networks or phase separation depending on the difference in the length of their alkyl chains. 2D co-crystallization can only be realized for BIC-C6/BIC-C10 or BIC-C8/BIC-C12 which have a four-methyl unit difference in their alkyl chains. The size complementarity of the alkyl chains in the two components suggests that it is responsible for the 2D co-crystallization, though hydrogen bonding contributes a lot both to the pristine honeycomb network and to the hybrid co-crystal. This result is of importance for understanding the role of van der Waals interaction and its interplay with hydrogen bonding in 2D co-crystallization.